Team interdependence and turnover: evidence from the NFL. Issue 3 (30th September 2014) - L. Davis, Justin; Fodor, Andy; E. Pfahl, Michael; Stoner, Jason
Abstract : Purpose: – The purpose of this paper is to empirically investigate the interactive effect of turnover and task interdependence on performance in work teams. Based on pervious research, the authors contend that turnover will have a negative effect on team performance and this effect will be more pronounced as teams perform highly interdependent tasks. Design/methodology/approach: – Using longitudinal data from the National Football League (NFL), the authors empirically examine the effect of player turnover on NFL team performance (i.e. wins and losses in the subsequent year), and the difference in team performance based on the high/low task interdependence of the work team. Findings: – Findings suggest a negative impact of turnover on organizational performance, regardless of the interdependent nature of work team tasks. In addition, the negative influence of turnover is enhanced by the task interdependence within a team. Originality/value: – This is one of the few studies that examine task interdependence as a moderating variable of the turnover – team performance relationship. More specifically, by examining an industry with high team member turnover (i.e. The NFL), the findings from this study give practicing managers a guide as to which work teams managers should attempt to minimize turnover.